1995
DOI: 10.1111/j.1476-5381.1995.tb14904.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the interaction between muscarinic M2 receptors and β‐adrenoceptor subtypes in guinea‐pig isolated ileum

Abstract: 1 Contraction of guinea-pig ileum to muscarinic agonists is mediated by M3 receptors, even though they account for only 30% of the total muscarinic receptor population. The aim of this study was to characterize the biochemical and functional effects of stimulation of the predominant M2 muscarinic receptor (70%) and to investigate the hypothesis that M2 receptors specifically oppose P-adrenoceptormediated effects in the ileum.2 In guinea-pig ileal longitudinal smooth muscle slices, isoprenaline, a non-selective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
42
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 26 publications
(38 reference statements)
2
42
0
Order By: Relevance
“…Eglen & Harris (1993) demonstrated that in the absence of elevated cyclic AMP and with an intact M3 receptor population, responses to (+)-cis-dioxolane in guinea-pig ileum did not involve M2 receptors. However, under experimental conditions where intracellular cyclic AMP is elevated, M2 receptor stimulation can elicit contractions or modulate adrenoceptorinduced relaxation by inhibition of adenylate cyclase in rat and guinea-pig ileum (Candell et al, 1990;Thomas et al, 1993;Reddy et al, 1994). Additionally, in other tissues such as the guinea-pig uterus it is the M2 muscarinic receptors through which a functional contractile response is mediated (Eglen et al, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…Eglen & Harris (1993) demonstrated that in the absence of elevated cyclic AMP and with an intact M3 receptor population, responses to (+)-cis-dioxolane in guinea-pig ileum did not involve M2 receptors. However, under experimental conditions where intracellular cyclic AMP is elevated, M2 receptor stimulation can elicit contractions or modulate adrenoceptorinduced relaxation by inhibition of adenylate cyclase in rat and guinea-pig ileum (Candell et al, 1990;Thomas et al, 1993;Reddy et al, 1994). Additionally, in other tissues such as the guinea-pig uterus it is the M2 muscarinic receptors through which a functional contractile response is mediated (Eglen et al, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the conditions in vitro are not favourable to the demonstration of an M 2 -response which involves the inhibition of adenylate cyclase. Indeed in guinea-pig ileum, responses normally mediated via M 3 -receptor can involve M 2 -activity following M 3 inactivation and elevation of cyclic AMP levels, the response then being regarded as a re-contraction or reversal of relaxation (Thomas et al, 1993;Reddy et al, 1995). This has also been shown in the rat bladder, but in this species the M 2 -receptor population is large (Hegde et al, 1997;Braverman & Ruggieri, 1999) and the M 2 : M 3 ratio is far greater than found in other species.…”
Section: Discussionmentioning
confidence: 99%
“…The urinary bladder, like the majority of other smooth muscles from many species, exhibit heterogeneous populations of muscarinic receptors (Hegde et al, 1997;Reddy et al, 1995). A predominance of the M 2 muscarinic receptor subtype, with a minor population of M 3 -receptors, has been reported for urinary bladder smooth muscle for several species.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations